Marine Heatwaves in Eastern Tropical Indian Ocean Basin: Long-Term Trend and Climate Variability - Mukti Trenggono; Sugianto, Denny Nugroho; Wirastriya , Anindya; Ismail , Muhammad Furqon Aziz; Yang , Yingyi; Wang , Dingqi (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research The basin has warmed consistently since the 1980s, with rising frequency, duration, and extent of events, most severe south of Java. Seasonal weakening of wind mixing during the Southeast Monsoon and transition months prolongs events, though daily intensity remains relatively stable. El Niño and positive Indian Ocean Dipole phases trigger basin-wide thermal anomalies, underscoring large-scale climatic control over event occurrence and strength. Reduced latent heat loss, enhanced surface thermal radiation, and weaker winds limit ocean cooling, reinforcing persistent surface warming and prolonged heatwaves.   Abstract Marine heatwaves in the Eastern Tropical Indian Ocean occur when sea surface temperature remains above its historical average for several consecutive days or weeks, disrupting marine ecosystems, affecting primary productivity, and reducing fishery yields through habitat degradation and altered species distribution. Despite their growing frequency and impact, the spatial and temporal variability of these events in the region remains poorly understood. This study examined their distribution, intensity, and long-term evolution, along with their relationship to regional climate variability, using high-resolution sea surface temperature data. Detection was performed at each grid point following the method of Hobday and key metrics were calculated to describe event duration and intensity. Empirical Orthogonal Function analysis was applied to identify dominant spatial patterns and temporal modes of variability. Results showed that these marine heatwaves occur about three times annually, with more frequent and prolonged events south of Java than west of Sumatra. Most were moderate in duration and intensity, peaking at around 3.25 days per month during the monsoonal transition, while the strongest intensities appeared in the Southeast Monsoon. Over the past decade, cumulative annual intensity increased significantly, showing a positive trend of 18.88 ± 8.33 °C days per decade. The dominant spatial mode revealed intensified events south of Java, while a secondary mode indicated an increase after the early 2000s. These findings demonstrate a growing intensification of marine heatwaves in the Eastern Tropical Indian Ocean, driven by reduced ocean heat loss and enhanced surface net thermal radiation, highlighting their potential to exacerbate thermal stress on regional fisheries and marine ecosystems under ongoing climate change.